The Critique Machine: Reconstructing the Production Process of Generic Critique in the Educational Sciences - Krönig, Franz Kasper (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2025)
This paper explores the extent to which critique in the educational sciences can be mechanized. This is the case when critique of pedagogical concepts and discourses is entirely determined by the structures and processes of the critique itself. If the process of critique functions independently of the specificity and concreteness of its object, the critique can be called generic and the critical system a trivial, that is, non-dynamic, machine. In these cases, the critique machine is cognitively closed and yields no information about the criticized concepts, structures, or phenomena. The paper argues that this, in fact, represents a significant proportion of critique in the educational sciences. The critique machine, as reconstructed here, consists of a sequence of four process stages. Finally, it is demonstrated that there are structural inconsistencies between these process stages.